2018
DOI: 10.1590/1413-70542018425000118
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium spp. genes and ORFs: Mechanisms and applications in plant science

Abstract: The bacterial origin of crown gall tumours, Agrobacterium tumefaciens was isolated 100 years ago. 70 years later, the findings that random integration of bacterial DNA into the host plant genome provided the potential of using Agrobacterium as a plant genetic engineering tool. Since the 1980s, Agrobacterium-mediated transformation on wide range of plants began developing rapidly. This review focused on the oncogenes of A. rhizogenes which is the causative agent of the hairy root disease and the application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 102 publications
0
8
0
1
Order By: Relevance
“…Moreover, the rolB geneencoded product was shown to exhibit tyrosine phosphatase activity (Filippini 1996;Dilshad et al 2015) and to interact with 14-3-3 proteins (Moriuchi et al 2004;Matveeva et al 2015), thus taking part in auxin signaling, enhancing the sensitivity of transformed cells toward auxin. It has been suggested that the product of rolC gene is a glucosidase liberating cytokinins from their bound forms (Estruch et al 1991;Rangslang et al 2018). Besides, the individual or combined rol genes are recognized to be an e cient activator of secondary metabolites biosynthesis in plants (Sarkar et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the rolB geneencoded product was shown to exhibit tyrosine phosphatase activity (Filippini 1996;Dilshad et al 2015) and to interact with 14-3-3 proteins (Moriuchi et al 2004;Matveeva et al 2015), thus taking part in auxin signaling, enhancing the sensitivity of transformed cells toward auxin. It has been suggested that the product of rolC gene is a glucosidase liberating cytokinins from their bound forms (Estruch et al 1991;Rangslang et al 2018). Besides, the individual or combined rol genes are recognized to be an e cient activator of secondary metabolites biosynthesis in plants (Sarkar et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…La bacteria, naturalmente incorpora genes que producen tumores o son inductores de la producción de hormonas vegetales en el huésped. Los biotecnólogos han reemplazado esos sitios y en su lugar insertan genes con algún interés de expresión (Rangslang et al, 2018). El sistema de A. tumefaciens y la entrega del plásmido Ti en la célula huésped se basa en el acompañamiento de varias proteínas que "escoltan" el ADN a través de la membrana del huésped y hasta el núcleo del mismo; a estas proteínas se les conocen como Vir, hay de varios tipos, cada una con una función específica.…”
Section: Flores Aromáticas: ¿Es Posible?unclassified
“…Numerous genes and open reading frames (ORFs) are present on the T L -DNA. The most well-known and characterized genes known to be involved in the compact habit and reduced plant growth, are the root oncogenic loci (rol) genes; rolA, rolB, rolC, and rolD, which correspond to ORFs 10, 11, 12, and 15, respectively (White et al, 1985;Slightom et al, 1986; reviewed by Rangslang et al, 2018;De Paolis et al, 2019). In comparison, the T R -DNA harbors aux1 and aux2 genes (iaaM and iaaH, respectively; Camilleri and Jouanin, 1991) involved in auxin biosynthesis (Mashiguchi et al, 2019) as well as a homolog of the rolB gene, termed rolBTr (Bouchez and Camilleri, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Plants can be regenerated from the hairy roots following treatment with various, often high, and ratios of cytokinins:auxins (Hegelund et al, 2017;Mandal et al, 2020;Neumann et al, 2020). Regenerated plants exhibit, among other features, compact habit, reduced plant growth, and frequently thicker leaves that are often reduced in size (as reviewed by Lütken et al, 2012a;Rangslang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%